Evaluation of Spatial Quality in Elderly Housing Facilities - Darvishi Postindoz, Zhila; Moosavi, Mir Saeed (European Journal of Sustainable Development, 2018)
The elderly population in Iran has dramatically increased in recent decades. Therefore, housing needs of the elderly are becoming more diverse than in the past, in terms of household types, economic status, health status, education level, family relationships, and housing experiences throughout their lifetimes. Most of older people expect to live in a house layout appropriate to their preferences. In reality, however, there is a lack of sufficient housing alternatives to suit their needs. Thus, various housing alternatives need to be developed to allow Iranian elderly to live as they like. This study surveyed the opinions of elderly housing facility staff in selected facilities to identify the opinions of residence-related characteristics and to investigate current problems, difficulties and improvement needs of the social issues and quality of physical space. Results of this study can provide useful information that can facilitate the improvement of alternative plans for elderly housing facilities in the future. Keywords: architecture, elderly, housing, quality.